The FastCarb project: Taking advantage of the accelerated carbonation of recycled concrete aggregates. (December 2022) - Torrenti, Jean Michel; Amiri, Ouali; Barnes-Davin, Laury; Bougrain, Frédéric; Braymand, Sandrine; Cazacliu, Bogdan; Colin, Johan; Cudeville, Amaury; Dangla, Patrick; Djerbi, Assia; Doutreleau, Mathilde; Feraille, Adelaïde; et al.
Abstract: Recycled concrete aggregates (RCA) incorporate hydrates that can be carbonated. The FastCarb project aims to mineralize CO2 within RCA, improving the quality of these aggregates by the clogging of the porosity and finally decreasing the CO2 impact of concrete in structures. It has two main objectives: to optimize in laboratory conditions the accelerated carbonation process which can be transposed at an industrial scale at a suitable cost and to show that the process could be used in industrial conditions. This paper presents firstly the results obtained in laboratory conditions: it confirms that it is possible to store between 10 and 50 kg of CO2 /t of RCA depending on several factors (natural carbonation, water content, temperature, size of RCA…) and that the treatment allows an improvement of the properties like the water absorption. The feasibility of accelerated carbonation has been also demonstrated by setting up two industrial-scale demonstrators. The first results without optimization showed a CO2 capture rate in the order of 3–4 %, i.e. 30 kg of CO2 per ton of crushed concrete. 80 t of carbonated RCA were produced and used to produce C25/30 and C45/55 concretes. The measurement of the main properties (performance in the fresh state, mechanical performance, and durability) shows that the use of the carbonated RCA doesn't affect these properties. A variety of precast products (blocks, curbs, stairs) and parts of cast-in-situ structures (construction of walls) were fabricated showing the feasibility of using these aggregates in real situations. Finally, our project considers whether the accelerated carbonation process is environmentally acceptable and economically viable. The first results show that the distance of transport (by trucks) is a major factor and that transportation should be limited to maintain a positive impact of the accelerated carbonation (i.e. local sources of CO2 should be used). The LCA and the economic study confirm that the sand fraction of RCA is the most interesting material for the uptake of CO2 . This is also interesting for a circular economy objective because recycled concrete sand is not easily used in concrete made with RCA.